(untitled) (Anclajes, 2025)
Based on the analysis of two stories from Javier Milanca’s book Xampurria, Somos del Lof de los que no tienen Lof (2015), this study addresses a series of problems related to representation and its political consequences in contemporary Mapuche life. These stories constitute a literary testimony that stands out for their recovery of historical events and experiences that intervene and challenge official narratives. Milanca enacts a critical operation linked to the restoration of subordinate memories of the Mapuche people, from a broad representation of violence. The categories of stench and cleanliness, along with the notion of biopoetics, enable an examination of how literature responds to the structured sedimentations imposed by dominant thought on Mapuche identity. These sedimentations are established through a set of common practices and representations framed within the concept of racism. To this end, this ideology is linked to the founding narrative of nations, which generates shared identifications and meanings.